Pengungkapan Emisi: Peran Tata Kelola, Modal, dan Manajemen Lingkungan - Novita WeningTyas Respati; Diah Novitasari (Politeknik Ganesha Medan, 2026)
This study examines the influence of capital expenditure, environmental management systems, institutional ownership, and independent boards of commissioners on carbon emission disclosure among companies in the IDX ESG Leaders Index for the 2021–2024 period. The analysis reveals that institutional ownership significantly and positively impacts emission transparency, confirming its role as a critical monitoring mechanism. However, other variables capital expenditure, environmental management systems, and independent boards did not reach statistical significance. These findings indicate that while institutional investors successfully drive disclosure, a gap still exists where other governance and investment structures remain merely administrative formalities. The results suggest that the ESG Leaders label requires stronger internal commitment beyond external shareholder pressure. Consequently, this study recommends the adoption of the emission-specific ISO 14064 standard and the establishment of dedicated sustainability committees to transform carbon disclosure from mere regulatory compliance into substantive corporate responsibility.